Pengembangan Model Bantuan Teknis, Fisik, dan Mental untuk Atlet Pencak Silat di Sekolah Menengah Atas Daerah - Moch. Ichdah Asyarin Hayau Lailin; Ratnaningrum Zusyana Dewi; Eko Sutrisno (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The increasing competitive demands in modern pencak silat require athletes to possess not only technical proficiency but also optimal physical conditioning and strong mental readiness. This study aims to develop an integrated assistance model that combines technical, physical, and mental aspects for pencak silat athletes in regional gymnasiums. The model was designed through a structured mentoring approach involving needs assessment, program planning, implementation, and evaluation within local training environments. Findings indicate that integrated assistance enhances technical execution, improves physical consistency, and strengthens athletes’ psychological readiness during competition. Mental training components, including confidence building and emotional regulation, play a crucial role in stabilizing performance under competitive pressure. The proposed model emphasizes the active role of coaches as technical instructors and psychosocial supporters. Overall, this integrated assistance model provides a practical and adaptable framework for improving athlete development in regional gymnasiums and contributes to sustainable, community-based sports performance development.